Edge morphology evolution of graphene domains during chemical vapor deposition cooling revealed through hydrogen etching. Issue 7 (1st February 2016) - Zhang, Haoran; Zhang, Yanhui; Zhang, Yaqian; Chen, Zhiying; Sui, Yanping; Ge, Xiaoming; Yu, Guanghui; Jin, Zhi; Liu, Xinyu
Abstract : The CVD cooling process induced graphene edge evolution, such as nanoparticle accumulation and graphene edge sinking. The results revealed the peculiar graphene–Cu movement during CVD cooling. Abstract : During cooling, considerable changes such as wrinkle formation and edge passivation occur in graphene synthesized on the Cu substrate. Wrinkle formation is caused by the difference in the thermal expansion coefficients of graphene and its substrate. This work emphasizes the cooling-induced edge passivation. The graphene-edge passivation can limit the regrowth of graphene at the domain edge. Our work shows that silicon-containing particles tend to accumulate at the graphene edge, and the formation of these particles is related to cooling. Furthermore, a clear curvature can be observed at the graphene edge on the Cu substrate, indicating the sinking of the graphene edge into the Cu substrate. Both the sinking of the graphene edge and the accumulation of silicon-containing particles are responsible for edge passivation. In addition, two kinds of graphene edge morphologies are observed after etching, which were explained by different etching mechanisms that illustrate the changes of the graphene edge during cooling.